CSO (Canadian Society of Otolaryngology – Head & Neck Surgery) position paper on return to Otolaryngology – Head & Neck Surgery Clinic Practice during the COVID-19 pandemic in Canada - Y. Chan; D. Angel; M. Aron; T. Hartl; S. P. Moubayed; K. A. Smith; D. D. Sommer; L. Sowerby; P. Spafford; D. Mertz; I. J. Witterick (Journal of Otolaryngology - Head and Neck Surgery)
Abstract The novel Coronavirus (COVID-19) has created a worldwide deadly pandemic that has become a major public health challenge. All semi-urgent and elective medical care has come to a halt to conserve capacity to care for patients during this pandemic. As the numbers of COVID-19 cases decrease across Canada, our healthcare system also began to reopen various facilities and medical offices. The aim for this document is to compile the current evidence and provide expert consensus on the safe return to clinic practice in Otolaryngology – Head & Neck Surgery. These recommendations will also summarize general precaution principles and practical tips for office across Canada to optimize patient and provider safety. Risk assessment and patient selection are crucial to minimizing exposure to COVID-19. Controversial topics such as COVID-19 mode of transmission, duration of exposure, personal protective equipment, and aerosol-generating procedures will be analyzed and discussed. Practical solutions of pre-visit office preparation, front office and examination room set-up, and check out procedures are explored. Specific considerations for audiology, pediatric population, and high risk AGMPs are also addressed. Given that the literature surrounding COVID-19 is rapidly evolving, these guidelines will serve to start our specialty back into practice over the next weeks to months and they may change as we learn more about this disease.